Double-Diffusive Natural Convection in L-Shaped Cavity by Lattice Boltzmann Method: Numerical Study - Kanna, Parthasarathy Rajesh; Satheesh, Anbalagan; Arumugam, Senthil Kumar; Öztop, Hakan Fehmi Fehmi; Devi, Neelamegam Rajan (Taylor & Francis Inc, 2025)
The double diffusive natural convection is studied numerically on an L-shaped cavity using lattice Boltzmann method (LBM). The top and right side of the cavity is insulated, the left and the bottom side of the cavity are maintained at high temperature, and remaining sides are considered as cold wall. This study is carried out using a two-dimensional nine-directional (D2Q9) lattice structure. Single relaxation time model is adopted to solve the LBM equations. The effects of different Rayleigh numbers (Ra = 103-105), aspect ratio (0.2-0.8), Prandtl number (Pr = 0.054, 0.7, 6.2, and 50), Lewis number (2), and buoyancy ratio (-2) on the temperature, concentration, and streamline contours are presented. For the selected range of operating parameters in this study, the heat and mass transfer are more pronounced for horizontal wall than vertical. At low Pr, the difference between horizontal wall to vertical wall average Nusselt number (Nu) is 11.2% and when Pr = 50, the same difference in average Nu is 37.5%. Similarly, the average Sherwood number between horizontal and vertical wall differences are 19.5% and 31.7%. For Ra = 105, the convection rate reduced by 46% and mass diffusion reduced by 52% between Pr = 0.054-50.
Keywords: Heat-Transfer; Magnetic-Field; Nanofluid; Enclosure; Simulation; Flow; Temperature; Behavior